Surgical emergencies in general practice - Scurr, John H. (1979)
Two thousand and thirty patients were seen in their own homes between 19.00 hours and 07.00 hours during a 14-month period. Twenty-nine per cent of these visits were for surgical conditions and a detailed analysis of this group is presented. An attempt to assess the necessity of the visit by grading them into minor, intermediate, and severe is also made. No attempt is made to discuss the treatment of individual conditions. The high admission rate to hospital probably reflects the uncertainty of further home follow-up.